Energy Transition from Fossil to Renewable Sources in North Africa: Focus on the Renewable Electricity Generation in Morocco - El Ghazi, Firdaous; Sedra, Moulay Brahim; Akdi, Mahmoud (International Journal of Energy Economics and Policy, 2021)
The aim of this article is to study the context and the challenges of the North African region in its quest towards energy transition. This work performs firstly a benchmark between the countries namely Algeria, Egypt, Morocco, and Tunisia, in terms of fossil resources and renewable potential based on official data and statistics. The study then focuses on Morocco, who is developing a new energy transition model axed on renewable electricity generation. In order to highlight the importance of legislation and economic evolution, the study compares the high with medium voltage renewable electricity market. In fact, a framework law has been established allowing private investors to benefit from the national electricity grid to inject and sell high voltage renewable electricity. Not being the case for medium voltage, the electricity transition for this market is depending on its own business model and economic profitability, therefore, a financial profitability study is further conducted to evaluate medium voltage photovoltaic competitiveness. The study concludes with the profitability impact assessment if 50% of the investment amount is subsidized by state or any other organization. The results of this study are discussed considering the current legislative context, it demonstrates the importance of subsidies and state legislation to accelerate the energy transition towards renewable energy development. Keywords: Renewable Energy sources, Photovoltaic electricity, Electricity transition, Profitability, Cash flow, Payback, Subsidies. JEL Classifications: Q4, Q5, K2 DOI: https://doi.org/10.32479/ijeep.11036